2012
DOI: 10.1007/s00066-012-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of involved-field radiotherapy for patients with early stage Hodgkin’s lymphoma based on a central prospective review

Abstract: Central review of the diagnostic imaging and clinical findings of Hodgkin's lymphoma patients shows a considerable number of discrepancies compared with the local evaluation. Thus, meticulous evaluation of all imaging information in close collaboration between the radiation oncologist and diagnostic radiologist is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Historically, quality assurance by the reference radiology and radiation oncology panel of the GHSG has proven to enhance both accuracy in diagnostic and therapy for HL. 11 , 12 , 14 The main reason for major deviations still lie within an inadequate coverage of an involved region which is in accordance with the literature. 11 , 12 A detailed recurrence analysis of the HD 16 trial showed that infield relapses constitute the major pattern of failures if RT is omitted in the treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Historically, quality assurance by the reference radiology and radiation oncology panel of the GHSG has proven to enhance both accuracy in diagnostic and therapy for HL. 11 , 12 , 14 The main reason for major deviations still lie within an inadequate coverage of an involved region which is in accordance with the literature. 11 , 12 A detailed recurrence analysis of the HD 16 trial showed that infield relapses constitute the major pattern of failures if RT is omitted in the treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Previous analyses on quality assurance have illustrated the importance of a systematic assessment of RT plans leading to harmonization and improvement of treatment concepts. 11 , 12 , 13 , 14 The aim of the present analysis is to continue this work and to examine whether the high standards of the GHSG could be maintained. One essential question was whether the transfer from IFRT to INRT within HD 17 was successful.…”
Section: Introductionmentioning
confidence: 99%